A study of Platelet Activation in Pre-Eclampsia - Ihsan, Imrana; Akram, Muhammad (Annals of King Edward Medical University, 2016)
The platelet behaviour during normal pregnancy seems to be quite modified like increased platelet aggregation, altered haemostatic mechanisms and enhanced fibrinolytic activity. The hyper-functioning endocrines and release of various platelet factors during pregnancy have been conjectured to cause the well-known features of pre-eclampsia. In order to evaluate the effects of pre-eclampsia on platelet behaviour, 125 women of child-bearing age were chosen from Services and Jinnah Hospitals, Lahore. The subjects/patients were grouped as control/non-pregnant (25), normal pregnant (50) and pre-eclamptic (50). Platelet aggregation study was performed on Aggregometer (Chronolog 540) and cell counts were performed on Coulter Counter Model T-660. It was observed that haemostatic mechanisms are stimulated during third trimester of normal pregnancy. The platelet reactivity remained unchanged despite a significant fall in platelet count. In pre-eclamptic group the platelet reactivity decreased significantly during third trimester. Platelet count also showed a highly significant decline in this group. The decreased responsiveness of platelets and fall in platelet count probably reflects platelet exhaustion. The routine performance of platelet function studies in pregnant women may help in predicting the onset of pre-eclampsia thereby providing a guideline for appropriate management of this condition.